Preliminary Clinical and Pharmacologic Investigation of Photodynamic Therapy with the Silicon Phthalocyanine Photosensitizer Pc 4 for Primary or Metastatic Cutaneous Cancers - Kinsella, Timothy J.; Baron, Elma; Colussi, Valdir; Cooper, Kevin; Hoppel, Charles; Ingalls, Stephen; Kenney, Malcolm; Li, Xiaolin; Oleinick, Nancy; Stevens, Seth; Remick, Scot (Frontiers in Oncology, 2011)
Photodynamic therapy (PDT) for cutaneous malignancies has been found to be an effective treatment with a range of photosensitizers. The phthalocyanine Pc 4 was developed initially for PDT of primary or metastatic cancers in the skin. A Phase I trial was initiated to evaluate the safety and pharmacokinetic profiles of systemically administered Pc 4 followed by red light (Pc 4-PDT) in cutaneous malignancies. A dose-escalation study of Pc 4 (starting dose 0.135 mg/m2) at a fixed light fluence (135 J/cm2 of 675-nm light) was initiated in patients with primary or metastatic cutaneous malignancies with the aim of establishing the maximum tolerated dose (MTD). Blood samples were taken at intervals over the first 60 hours post-PDT for pharmacokinetic analysis, and patients were evaluated for toxicity and tumor response. A total of 3 patients (2 females with breast cancer and 1 male with cutaneous lymphoma) were enrolled and treated over the dose range of 0.135 mg/m2 (first dose level) to 0.54 mg/m2 (third dose level). Grade 3 erythema within the photoirradiated area was induced in patient 2, and transient tumor regression in patient 3, in spite of the low photosensitizer doses. Pharmacokinetic observations fit a 3-compartment exponential elimination model with an initial rapid distribution phase ( 0.2 hrs) and relatively long terminal elimination phase ( 28 hrs), Because of restrictive exclusion criteria and resultant poor accrual, the trial was closed before MTD could be reached. While the limited accrual to this initial Phase I study did not establish the MTD nor establish a complete pharmacokinetic and safety profile of intravenous Pc 4-PDT, these preliminary data support further Phase I testing of this new photosensitizer.